How Islamic Securities Crowdfunding Platforms Attract Prospective Investors to SMEs: Insights from Indonesia (IQTISHADIA, 2024)
This study aims to explore the extent to which outbound Islamic brands encourage Muslim and non-Muslim investors to invest in Islamic FinTech securities crowdfunding (SCF) with perceived trust as a mediating variable. This study includes the results of an online survey of two hundred and twenty-five investors. Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis was employed to test the statistical hypothesis. This study shows that outbound Islamic brands are the main drivers for Muslim and non-Muslim investors to invest in Islamic securities crowdfunding platforms using smartphones, and brands that are perceived well by investors can also increase trust in SCF. On the other hand, The mediating effect of perceived trust is proven to have a significant impact on investment interest; thus, this finding provides in-depth insights for investors regarding effective investment strategies and encourages them to have more confidence in the potential of the FinTech market.